Why does theory of inventive problem solving matter in Malaysian food and beverage industry? - Zhengxiaoming, Aminaimu; Fernando, Yudi (KnE Social Sciences, 2019)
Nowadays, the competition in the food and beverage industry has developed from a single food competition to comprehensive competition in all aspects: from the pursuit of high-quality products to the expansion of market share, to the promotion of the brand effect and to the new shape of pursuing the entire enterprise. Consumers’ demands keep changing with the passage of time. These changes are different from demands that occurs for classy foods requiring typical features such as nutrition value, lusciousness of taste, and accessibility, to basic aspects such as improved food safety, food life span, durability, and waste food proper management. Thus, the objective of this research work is to review the TRIZ-theory of inventive problem solving matter in Malaysian food and beverage industry. The new product development in Malaysian food and beverage industry need to accommodate the market demand. This study revealed that the actual product development process can be analysed by assessing the interactions between consumer demands and expectations, the producer’s technical capacity of the food, and emerging knowledge from scientific researches about food. This has been attributed to the problem of low quality of input terms of the food industries and productivity growth of Malaysian manufacturing industries, which is actually input-driven rather than total factor productivity-driven.